The perilous riding behavior and accident of motorcycles in university students - Fera Atmawati; Nurhalisa Nurhalisa; Wa Ode Sri Mulyani; Muhammad Reza Adyatama Pimpie; Walid Wahyudin Rahman (Public Health of Indonesia)
Background: An inevitable traffic accident frequently resulted from the dereliction of individualized community from disobeying regulation which causes an impact on the safety of another person. The impact raised is not merely in terms of material but also non-material.